Circumstantial Adjunct used in the Novella “A Reason to Rain” by Donna M. Young - Bunga Rifka Bintara (English Teaching and Linguistics Journal (ETLiJ), 2022)
This research aims to describe the different types of circumstantial adjuncts and the primary forms of circumstantial adjuncts identified in Donna M. Young's novella "A Reason to Rain." The researcher looked at several forms of circumstantial adjuncts in Donna M. Young's novella "A Reason to Rain" along with the instances identified. The descriptive qualitative method was employed in this investigation. The information comes from "A Reason to Rain," a novella. After reading the novella via pdf entitled "A Reason to Rain" by Donna M. Young, the researchers found 117 circumstantial adjuncts used in the novella. After that, the researcher classified the types of circumstantial adjuncts in the novella by using Halliday's theory. Then, using the percentage formula, the researcher calculates the percentage of the circumstances. The study's finding shows that this novella has seven circumstantial adjuncts types, including place, level, role, manner, accompaniment, cause, and content. However, there are no contingency and angle adjuncts in this novella. Furthermore, location adjuncts were discovered to be the most prominent affixes, accounting for 42.57 percent of all circumstantial adjuncts.